Agenesis of the Gallbladder in Monozygotic Twin Sisters - Koki Hoshi; Atsushi Irisawa; Goro Shibukawa; Akane Yamabe; Mariko Fujisawa; Ryo Igarashi; Ai Sato; Takumi Maki (Case Reports in Gastrointestinal Medicine)
Agenesis of the gallbladder, a rare anomaly, is generally regarded as an organogenic failure. Several reports suggest that this congenital defect is inherited but that supposition remains controversial. We described agenesis of the gallbladder in identical twins. A 21-year-old female presented with a history of acute pain in the epigastrium and right hypochondrium. Various imaging modalities showed “gallbladder agenesis.” Moreover, her older identical twin sister had also no visualized gallbladder in imaging modalities. This case report strongly suggested that agenesis of the gallbladder would be caused by a genetic abnormality.